Comparação entre a circulação de cepas de streptococcus pneumoniae, casos de pneumonia adquirida na comunidade em crianças, antes e após a implementação da vacina pneumocócica, no estado do Pará - NAVES, Bárbara Caroline Dias (2023)
Introduction: Community-acquired pneumonia (CAP) has Streptococcus pneumoniae as its main bacterial etiological agent. In Brazil, about 34,000 hospitalizations for pneumococcal diseases were registered between 2004 and 2006, and pneumococcal pneumonia accounted for 64.8% of these hospitalizations. The 10-valent pneumococcal conjugate vaccine (PCV10) was implemented in routine vaccination of Brazilian children up to 2 years of age in March 2010, with Brazil being the first country to introduce the vaccine into the National Immunization Program. Objective: The objective of this study was to compare the circulation of S. pneumoniae strains causing CAP, to characterize invasive strains by susceptibility to antibiotics and to estimate the impact on the number of hospitalizations and deaths caused by CAP in children between 1 month and 35 months before and after the implementation of the 10-valent pneumococcal vaccine in the State of Pará. Methodology: This is a descriptive, retrospective and population-based study. In the period prior to the introduction of the PCV10 vaccine, PAC cases were collected through daily active surveillance, performed in eight public and private hospitals throughout the region of Belém, where bacterial isolation results were evaluated. For the purposes of comparison with post-vaccination information, covering the characteristics of strains of S. pneumoniae circulating in Brazil, data available from the System of Surveillance Networks of Agents Responsible for Bacterial Pneumonias and Meningitis (SIREVA II - Brazil) were consulted. Data on admissions and deaths caused by PAC in the State of Pará were obtained through the SUS Hospital Information System (SIH / SUS). Results: In Belém, before the introduction of the PCV10 vaccine, serotype 14 was predominant, representing 63.6% of the isolates. The other serotypes found were 23B, 23F, 3 and 6B. After the implementation of the vaccine there was reduction of serotype 14, 6B, 23F and significant increase of 19A. Serotypes 3 and 6C remained among the most detected. In Belém, resistance to the antibiotic sulfamethoxazole-trimethoprim, levofloxacin and tetracycline was observed in 45.5% of the cases isolated through active surveillance in the pre-vaccine period. In the post-vaccination period, the data also showed greater resistance to the antibiotic sulfamethoxazole-trimethoprim, as well as to erythromycin. Data from hospitalizations for pneumonia in children aged 0 to 4 years in the State of Pará showed a marked reduction in the number of hospitalizations in the period after the implantation of the PCV10 vaccine, mainly until the year 2016. Conclusion: Circulation of S. pneumoniae strains causing CAP, presented a change in the period after the implementation of the PCV-10 vaccine, with a decrease in the circulation of strains characterized as 14, 6B and 23F, present in PCV-10, there was an increase in the prevalence of serotypes 19A and 3, which are not included in the vaccine. The antimicrobial resistance of S. pneumoniae strains remained, especially against the antibiotic sulfamethoxazole-trimethoprim. There was a marked reduction in the number of hospitalizations for PAC, but a modest reduction in infant mortality in the state of Pará. The greatest reductions in PAC mortality in Brazil occurred in low income populations